Human Capital and Competences in Project Management - Otero-Mateo, Manuel; Pastor-Fernandez, Andres (IntechOpen, 2018)
People's competence has a strong influence on the strategy of human resource management, affecting daily aspects, thought patterns, and behavioral modes of executive management and employees. From a business perspective, there is a strong relationship between human capital and success and also an integral development of the human factor in all its dimensions, both personal and professional, and social competences must be a key factor to reach it. To help achieve this business excellence, it is necessary to transfer the demands of the labor market into education, and one of the ways is through methodological framework for Project Management and Management, specifically the IPMA Individual Competence Baseline, which is an essential tool for achieving economic growth, corporate development, and competitiveness.